Effect of silane treatment on mechanical properties and thermal behavior of bamboo fibers reinforced polypropylene composites - Wang, Qianting; Zhang, Yu; Liang, Weikang; Wang, Jianjie; Chen, Youxin (Journal of engineered fibers and fabrics, 2020)
In this work, the surface of the bamboo fibers (BF) was treated with three kinds of silane coupling agents terminated with amino functional groups (KH550), epoxy functional groups (KH560), and methyl functional groups (KH570) to improve fiber–matrix adhesion. The effects of silane treatment on the mechanical properties and thermal behavior of BF/polypropylene (PP) composites were investigated. Mechanical test results showed that the order of modification effectiveness was KH570 > KH550 > KH560. KH570 treated fiber composite exhibited the best mechanical properties. The tensile strength and flexural strength of 5 wt% KH570 treatment reached to 36.1 and 54.7 MPa, which were 15.4% and 23.6% higher than those of UBF/PP composites. Simultaneously, the thermal stability increased from 467.0°C (UBF) to 470.6°C (KH-570 treated BF). An increase in crystallization temperature (1.7°C) and a decrease in crystallinity (5.8%) occurred upon the addition of 5% KH570 silanes treated bamboo fibers.